Study on the mechanism of areca alkaloids against eimeria tenella - Xuan Li; Pan Hu; Wei Liu; Hongquan Li; Jianguo Zeng (Poultry Science, 2025)
Avian coccidiosis (AC) is a parasitic disease caused by the protozoan parasite Eimeria tenella (E.tenella), which primarily parasitizes the cecum of chickens, resulting in a reduction of their production capacity. Areca alkaloids(AAl), derived from the plant Areca catechu L, have been repeatedly reported to exhibit anti-parasitic effects against protozoa, this suggests its potential efficacy in combating E.tenella. The purpose: of this study is to explore the mechanism underlying the anti E.tenella effects of AAl. Methods: Screening potential active ingredients of AAl by establishing an Eimeria tenella spores(ETs) infection model of extracellular chicken cecal epithelial cells. Confirm the anti E.tenella effect of potential active ingredients through in vivo experiments on broiler chickens, HE stained sections of cecal tissue, immunofluorescence staining, and Elisa inflammatory immune index detection. The results: indicate that arecoline and homoarecoline exhibit significant in vitro anti E.tenella activity. Electron microscopy observations revealed that these two compounds can disrupt the apical structure of E.tenella spores. Molecular docking studies demonstrated that the common targets of these two compounds are the acrosomal protein AMA 1 and filamentous protein MIC 3 of ETs. Homoarecoline binds to a greater number of E.tenella targets. Both compounds showed efficacy in the anti coccidiosis index (ACI) evaluation of chicken models infected with E.tenella., Neither compound induced an increase in sIgA levels in the cecum of chickens. In summary: this study elucidates the primary active ingredients and molecular targets of AAl against E.tenella, suggesting that arecoline and homoarecoline may serve as potential therapeutic agents for E.tenella infection.